Type 1 interferon signature and allograft inflammatory factor-1 contribute to refractoriness to TNF inhibition in ankylosing spondylitis - Woogil Song; Eunyoung Emily Lee; Seongwan Park; Baekgyu Choi; Min-Gang Kim; Seo Yoon Ban; Se Rim Choi; Jeong Yeon Kim; Seon Uk Kim; Jong-Il Kim; Eui-Cheol Shin; Inkyung Jung; et al. (Nature Communications)
Abstract Ankylosing spondylitis (AS) is a chronic inflammatory arthritis that primarily affects the enthesis and may culminate in bony ankylosis of the spine. Despite TNF inhibitor (TNFi) being foundational in managing active inflammation, 30-40% of patients with AS remain non-responsive. Through longitudinal and multi-omics profiling of peripheral blood mononuclear cells from TNFi-receiving patients with AS, here we reveal that elevated type I IFN signatures at baseline are associated with poor TNFi response, leading to a paradoxical enhancement of IFN signatures and Th17 responses following TNFi therapy. Among type I IFN-related genes, we identify and validate AIF-1 as a predictive biomarker reflecting the inherent IFN signature that differentiates responders from non-responders. AIF-1 also contributes to an inflammatory cycle by increasing IFNα receptor expression and Th17 responses. In summary, our findings advocate for a personalized approach to managing AS by considering individual variations in AIF-1 levels and IFN signatures.